Analisis Pemahaman Konsep Fisika Peserta Didik Kelas X IPA di SMA Negeri 1 Manokwari melalui Pembelajaran Online - Dian Novitasari; Sri Wahyu Widyaningsih; Sri Rosepda Br. Sebayang (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2021)
This study aims to analyze student’s understanding of the physical concepts in class X IPA SMA Negeri 1 Manokwari through the online learning. The research method used is a survey method using a test instrument. The sampling technique used was purposive sampling with the test sample was 66 students from the first 2 classes who completed the material and the research sample was 219 students from the other 7 classes. The instrument used in this study was a test of understanding the concept of physics which was made and arranged by paying attention to the cognitive process of understanding the concept which consisted of 17 valid questions. The results of the analysis showed that the student’s ability to understand the physics concepts of class X IPA at SMA Negeri 1 Manokwari on Newton’s law material about straight motion were divided into five categories. The very high category was 4%, the high category was 20%, the moderate category was 39%, the low category was 25% and the very low category was 12%. The most visible understanding of the physics concepts is the cognitive process of interpreting with a percentage of very high and high ability students of 57,1%.